Impacts of Invasive Australian Acacias on Soil Bacterial Community Composition, Microbial Enzymatic Activities, and Nutrient Availability in Fynbos Soils - Keet, Jan-Hendrik; Ellis, Allan G; Hui, Cang; Novoa, Ana; Le Roux, Johannes J (Microbial ecology, 2021)
Invasive plants often impact soil conditions, notably through changes in soil chemistry and microbial community composition, potentially leading to altered soil functionality. We determine the impacts of invasive nitrogen-fixing Australian Acacia trees on soil chemistry and function (carbon, nitrogen, and phosphorus cycling) in South Africa's Core Cape Subregion, and whether any differences in soil function are linked to differences in soil chemical properties and bacterial community composition between neighbouring acacia-invaded and uninvaded sites. We do so by using Illumina MiSeq sequencing data together with soil chemistry and soil enzyme activity profiles. Acacias significantly increased levels of soil nitrogen (NO3-, NH4+, and total N), C, and pH. Although we did not find evidence that acacias affected soil bacterial community diversity, we did find them to alter bacterial community composition. Acacias also significantly elevated microbial phosphatase activity, but not β-glucosidase, whilst having contrasting effects on urease. Changes in soil chemical properties under acacia invasion were found to correlate with changes in enzyme activities for urease and phosphatase. Similarly, changes in soil bacterial community composition were correlated to changes in phosphatase enzymatic activity levels under acacia invasion. Whilst we found evidence for acacias altering soil function by changing soil chemical properties and bacterial community composition, these impacts appear to be specific to local site conditions.
Keywords: Enzyme activities; Australian acacias; Nutrients; akácie; Acacia; Microbiota; Invasion; Soil Microbiology; Australia; Soil function; půdní mikrobiologie; Soil microbial ecology; Austrálie; mikrobiota; půda; živiny; Soil; Fynbos; 16S rDNA